A reevaluation of population and nesting density estimates of the Philippine eagle pithecophaga jefferyl in Mindanao using Voronoi diagram - Alegarbes, Daryl R.
The Philippine Eagle is one of the most endangered species in the world (Philippine Eagle, undated). Studies have been done to estimate the remaining population of the species. Buesser et.al. (2001) estimated the nesting density at 130 km2 and the population at 82-146 pairs of the eagles in Mindanao using hypothetical circular territories that overlap. Based on the assumption that the territories are non-overlapping polygons, this paper determined the territory shape and computed the territory size for each pair of eagles. The population and nesting density were also computed. Transformation as well as verification of data was done to remove redundancy. Then the Voronoi Diagram was computed. The resulting diagrams were then plotted over the vegetation map. The forest cover bound the diagrams. Computation of the area was done manually by using square grids of 0.4 cm2 : 1 km2 since the resulting bounded. Voronoi cells were irregular and nonconvex polygons. Statistical measures were then computed. Due to high variability of the data, the mean was not a good measure of central location. Using the median of 59.5 ? 76.5 km2 and using ratio and proportion, an estimated population of 176-229 breeding pairs of Philippine Eagles was computed. Comparing to the estimated population of 82-146 eagles of the study of Bueser et.al. (2001), it can be concluded that their estimate may have been an underestimation